Analisis Perhitungan Pajak Pertambahan Nilai dan Pajak Penghasilan Pasal 22 Terhadap Pajak Terutang Pada PT. Sumber Mitra Ramothy - Murdan Sianturi; Vika Alviyani (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
This research was conducted at PT. Sumber Mitra Ramothhy whose address is Ruko Cibubur Indah Blok F No. 12, Jl. Shooting Range, East Jakarta. This study aims to find out how the calculation of Value Added Tax (VAT) and Article 22 Income Tax, is it in accordance with the Laws and Tax Regulations and their effect on the Tax Payable at PT. Sumber Mitra Ramothy. The research method used in this study is a quantitative and descriptive analysis method. The results of the analysis show that it is known that the total purchases of goods during 2021 amounted to Rp 6,959,853,782 and the total sales of goods during 2021 amounted to Rp 14,241,522,200. From the calculations that have been done by the author, the amount of VAT payable is Rp 661,969,891 and the amount of Income Tax Article 22 is Rp 108,127,705. The calculation and collection of VAT and Article 22 Income Tax by the company are in accordance with the Laws and Tax Regulations. However, there are still errors in recording the calculation of VAT payable. There are overpayments on Output VAT due to data recording errors that should not be recorded in July amounting to Rp. 1,049,990 and in October amounting to Rp. 23,994, there are also overpayments due to unrecorded sales returns of Rp. 5,078,821 and underpayments due to not recorded at Rp 24,003 in November, so it has a direct effect on the tax payable.